2022
DOI: 10.1002/pc.26636
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of physico‐mechanical, thermal, morphological, optical and biodegradation properties of polyvinyl alcohol films reinforced with alkali treated Limonia acidissima shell powder

Abstract: Polyvinyl alcohol (PVA) and various concentrations of (5–25 wt%) alkali treated Limonia acidissima shell powder (LASP) was utilized to develop bio composite packaging films by solution casting method. The alkali treatment (5%NaOH) of the LASP particles were carried out to improve the interface adhesion between filler and PVA matrix and also remove non cellulosic contents from LASP. The biofilms were characterized by Fourier‐transform infrared spectroscopy, X‐ray diffraction analysis, thermogravimetric analyzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…The elongation at break (EB) was found to be decreased to 50.3 (pure PVA film), 12.77, 9.39, 6.14, and 5.15% with the addition of 5−20 wt % of CPSP in the PVA matrix. The trend observed in the elongation at break in the study was similar to the loading of LASP 35 and green banana peel powder 36 with PVA described in previous studies. The mechanical properties and thicknesses of film samples are listed in Table 4.…”
Section: ■ Results and Deliberationsupporting
confidence: 89%
See 1 more Smart Citation
“…The elongation at break (EB) was found to be decreased to 50.3 (pure PVA film), 12.77, 9.39, 6.14, and 5.15% with the addition of 5−20 wt % of CPSP in the PVA matrix. The trend observed in the elongation at break in the study was similar to the loading of LASP 35 and green banana peel powder 36 with PVA described in previous studies. The mechanical properties and thicknesses of film samples are listed in Table 4.…”
Section: ■ Results and Deliberationsupporting
confidence: 89%
“…37 A better film barrier quality was the principal outcome of the stuffing action of agrowaste particle fillers. Another inves- tigation showed that incorporating the alkali-treated LASP 36 improved the opacity of a biopolymer-based film. The agglomeration of CPSP at higher loading proportions in the PVA matrix was primarily responsible for the decrease in transmittance at 800 nm and the increase in crystallinity generated by increasing the CPSP concentration in the film.…”
Section: ■ Results and Deliberationmentioning
confidence: 99%
“…This is because of the environmental pollution and health hazards possessed by the man‐made synthetic fibers used as reinforcement in spite of their excellent mechanical properties. Over a decade, the use of natural fiber composites has seen tremendous growth in the automobile sector and lightweight structural applications 4 . In order to support this industrial scenario research, needs to be focused on ensuring the sustainability of raw materials for industries without affecting the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Over a decade, the use of natural fiber composites has seen tremendous growth in the automobile sector and lightweight structural applications. 4 In order to support this industrial scenario research, needs to be focused on ensuring the sustainability of raw materials for industries without affecting the environment. Utilizing natural fibers from agro-waste for reinforcement in polymer composites reduces the need for harvesting plants for natural fibers which might remain as food for herbivorous animals.…”
Section: Introductionmentioning
confidence: 99%
“…The water vapor transmission coefficient was used to assess how well nanocomposite films performed as a water vapor barrier (WVP). The WVP was measured according to ASTM standard method E96‐95 27 : before the test, the composite films sample stayed 48 h in a setting with a relative humidity of 50% and a temperature of 25°C. Then, The film sample was sealed at the mouth of the weighing bottle with tape after a specific volume of anhydrous silica gel was weighed and added to the 25 mm × 40 mm weighing bottle.…”
Section: Methodsmentioning
confidence: 99%